Beyond the social license to operate: Whole system approaches for a socially responsible mining industry. (January 2022) - Verrier, Brunilde; Smith, Carl; Yahyaei, Mohsen; Ziemski, Marcin; Forbes, Gordon; Witt, Kathy; Azadi, Mehdi
Abstract: The demand for minerals, metals and rare-earth elements is rapidly growing to support the transition to low-carbon energies, and the mining industry must increase its supply while facing complex Environmental, Social and Governance (ESG) risks. Traditionally relying on its engineering expertise to maximize ore extraction, the sector must now find ways to sustain its production while facing increased scrutiny from the public, civil societies and shareholders alike. The paper reviews current practice in sustainability assessment to highlight sector-specific characteristics and the notion of trust as central to effective project developments. Because the social interface of extractive operations is complex, dynamic and non-linear in nature, we recommend going beyond the aim of obtaining a social license to operate and use Systems Thinking to fully embed Corporate Social Responsibility (CSR) at the core of strategic mine planning. System Dynamics can foster interdisciplinary collaborations by bridging together social and technical flows within simulation models to identify sustainable levers of change. We present the development of a stock and flow model quantifying causal mechanisms between the use of cyanide, the environment, communities and public trust, and operational productivity. Industry practitioners, researchers and facilitators can use the model as an adaptable framework to engage with systems modelling in mining. We recommend its use in conjunction with meaningful stakeholder's engagement to ensure shared understanding, reduced uncertainty and long-term benefits for all.